Psychotherapy and the highly sensitive person eaudiobook Improving outcomes for that minority of people who are the majority of clients. - Aron, Elaine N. (Tantor Media, 2019)
Dr. Elaine Aron's book Psychotherapy and the Highly Sensitive Person redefines the term "highly sensitive" for the professional researcher and practitioner. She dispels common misconceptions about the relationship between sensitivity and other personality traits, such as introversion and shyness, and further defines the trait for the benefit of both the clinician and patient. Listeners will learn to assess for the trait, distinguish it from clinical diagnoses such as panic disorder or avoidant personality disorder, understand how sensitivity may change the presentation of a problem such as depression or shyness, and generally inform, validate, and improve the quality of life for these clients. She pays particular attention to self-esteem issues and helping patients separate effects of their innate temperament from problems due to their personal learning histories. Dr. Aron keeps both patient and practitioner in mind as she suggests ways to adapt treatment for highly sensitive persons and how to deal with the typical issues that arise. Through this helpful guide, therapists will see a marked improvement in their ability to assist highly sensitive clients.